Improving the Safety Management System to Reduce the Risk of Workplace Accidents on the MT. Stargaze Ship - Jonathan Marco Putera Jacobus; Elise Dwi Lestari; Natriya Faishal Rachman; Tri Haryanto (Cita konsultindo, 2026)
This study aims to analyze the factors that hinder safety management and the efforts needed to improve the safety management system in order to reduce the risk of occupational accidents on board MT Stargaze. This research used a qualitative method with observation, interviews, and documentation techniques. The study was conducted over 12 months, starting on 23 July 2024 when the researcher departed from Singapore and ending on 23 July 2025 in Indonesia. Observations focus on the use of Personal Protective Equipment (PPE), the implementation of safety meetings, safety drills, work supervision, filing practices, and the maintenance of safety equipment. Secondary data were obtained from PPE inventory records, safety meeting notes, drill lists, the deck logbook, inspection reports, and maintenance records for safety equipment during the research period. The findings show that safety management on board has been implemented, but inconsistencies remain in PPE usage, limited understanding among some crew members regarding safety procedures, and document filing that is not yet fully orderly. These findings are supported by interviews and documentation, which indicate the continuing need for guidance, stronger supervision, and disciplined work practices. The necessary improvement efforts include routine coaching, stricter officer supervision, better reporting discipline, and ensuring that safety equipment is always ready for use so that the safety management system can operate more effectively